Cronies, procrastinators, and leaders: A conservation of resources perspective on employees' responses to organizational cronyism. Issue 1 (2nd January 2022) - De Clercq, Dirk; Fatima, Tasneem; Jahanzeb, Sadia
ABSTRACT: This article draws from conservation of resources theory to detail a critical mediating role of organizational disidentification in the connection between employees' perceptions of organizational cronyism and their procrastination, as well as a buffering role of leader–member exchange in this process. Three-wave, time-lagged data collected from employees across multiple industry sectors indicate that an important reason that beliefs about favouritism-based organizational practices escalate into enhanced procrastination behaviour is that employees feel embarrassed about their organizational membership. Yet this mediating role of organizational disidentification is less prominent to the extent that employees can draw from high-quality relationships with their immediate supervisor. For organizations, this study reveals a key mechanism – employees' psychological distancing from their employing organization – by which dysfunctional organizational favouritism can escalate into a tendency to slack off in their job tasks, and it pinpoints how this risk can be contained by high-quality supervisor exchanges.